Flux Crystal Growth of the Ternary Polygermanide LaPtGe2, a p‐Type Metal. Issue 12 (20th March 2015) - Bugaris, Daniel E.; Sturza, Mihai; Han, Fei; Im, Jino; Chung, Duck Young; Freeman, Arthur J.; Kanatzidis, Mercouri G.
Abstract: Large plate crystals of LaPtGe2 have been grown by using an inert indium metal flux. This compound crystallizes in the CeNiSi2 ‐type structure (orthorhombic space group Cmcm ) with lattice parameters a = 4.3770(9) Å, b = 17.186(3) Å, and c = 4.3942(9) Å. The structure of LaPtGe2 is a three‐dimensional framework with alternating PbO‐type layers of PtGe and infinite Ge chains, separated by La atoms. Electrical resistivity and Hall effect measurements characterize LaPtGe2 as a metal with holes that act as the charge carriers. Strong temperature dependence of the Hall coefficient and a violation of Kohler's rule (from magnetoresistance data) both indicate possible multiband effects. The electronic structure calculations suggest the metallic nature of LaPtGe2 and show that the strongest bonding exists between Pt and Ge within the PbO‐type layers. Abstract : Plate crystals of LaPtGe2 have been grown from a molten indium flux. This compound crystallizes in the CeNiSi2 ‐type structure. Electrical resistivity, Hall effect, and thermopower measurements have shown that LaPtGe2 exhibits p‐type metallic behavior, which is consistent with electronic band structure calculations.